1999
DOI: 10.1021/ma990177h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Segmental Swelling Ratio of a Symmetric Block Copolymer on the Morphology of Melt-Mixed Immiscible Polymer Blends

Abstract: We investigate droplet breakup and coalescence under shear flow for an immiscible polymer blend system in which styrene-acrylonitrile random copolymer and poly(cyclohexyl methacrylate) are the blend components, and a symmetric poly(styrene-b-methyl methacrylate) block copolymer (bcp) is utilized as a compatibilizer. The influence on the blend morphology of the ratio (S r) between the swelling power at the interface of the bcp segment outside the droplet versus that inside the droplet is studied. We find that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Other studies have concluded27, 29, 30 that copolymers with substantially shorter blocks can show high efficiency. The rule for the prediction of compatibilization efficiency suggested by Kim et al31 is not applicable to systems with block lengths substantially shorter than the lengths of the compatibilized chains. Recently, the compatibilization efficiency of a set of model block copolymers, with different numbers of blocks and with styrene blocks of different lengths, in blends of PS with various polyolefins has been studied 32–39.…”
Section: Introductionmentioning
confidence: 95%
“…Other studies have concluded27, 29, 30 that copolymers with substantially shorter blocks can show high efficiency. The rule for the prediction of compatibilization efficiency suggested by Kim et al31 is not applicable to systems with block lengths substantially shorter than the lengths of the compatibilized chains. Recently, the compatibilization efficiency of a set of model block copolymers, with different numbers of blocks and with styrene blocks of different lengths, in blends of PS with various polyolefins has been studied 32–39.…”
Section: Introductionmentioning
confidence: 95%
“…Kim et al20 suggested, using the ratio of the swelling power at the interface of the block copolymer segment outside the droplet to that inside the droplet, S r , for prediction of the compatibilization efficiency. Using the results for the poly(cyclohexyl methacrylate)/poly(styrene‐ ran ‐acrylonitrile) blend compatibilized with poly(styrene‐ block ‐methyl methacrylate) diblock copolymer, they concluded that block copolymers are inefficient emulsifiers if S r < 0.4 or S r > 2.5.…”
Section: Introductionmentioning
confidence: 99%
“…It cannot be a priori excluded that the PS/PB ratio is one of the parameters controlling the effect of SB on the structure and properties of PS/PE/SB blends. On the other hand, it seems from thermodynamic analysis that the distribution of a block copolymer between the interface and bulk phases is determined by the ratios of the block length and the related blend components and their interaction parameters 22. The direct effect of the ratio of plastic PS and rubbery PB in SB copolymers on the impact strength of PS/PE/SB blends should be apparently stronger than that on their morphology and flow properties.…”
Section: Resultsmentioning
confidence: 99%